Emerging cellular themes in leukodystrophies - Nowacki, Joseph C.; Fields, Ashley M.; Fu, Meng Meng (Frontiers in Cell and Developmental Biology, 2022)
Leukodystrophies are a broad spectrum of neurological disorders that are characterized primarily by deficiencies in myelin formation. Clinical manifestations of leukodystrophies usually appear during childhood and common symptoms include lack of motor coordination, difficulty with or loss of ambulation, issues with vision and/or hearing, cognitive decline, regression in speech skills, and even seizures. Many cases of leukodystrophy can be attributed to genetic mutations, but they have diverse inheritance patterns (e.g., autosomal recessive, autosomal dominant, or X-linked) and some arise from de novo mutations. In this review, we provide an updated overview of 35 types of leukodystrophies and focus on cellular mechanisms that may underlie these disorders. We find common themes in specialized functions in oligodendrocytes, which are specialized producers of membranes and myelin lipids. These mechanisms include myelin protein defects, lipid processing and peroxisome dysfunction, transcriptional and translational dysregulation, disruptions in cytoskeletal organization, and cell junction defects. In addition, non-cell-autonomous factors in astrocytes and microglia, such as autoimmune reactivity, and intercellular communication, may also play a role in leukodystrophy onset. We hope that highlighting these themes in cellular dysfunction in leukodystrophies may yield conceptual insights on future therapeutic approaches.